2015
DOI: 10.3892/ol.2015.3562
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of hepatitis B surface antigen-negative and hepatitis C antibody-negative hepatocellular carcinoma

Abstract: Abstract. The present study investigated the clinicopathological characteristics of resected hepatitis B virus surface antigen (HBs-Ag)-negative, hepatitis C virus antibody (HCV-Ab)-negative hepatocellular carcinoma (NBNC HCC). The clinicopathological characteristics of 164 patients with NBNC HCC, 144 patients with HBs-Ag-positive HCC (HBV group) and 550 patients with HCV-Ab-positive HCC (HCV group) were compared. In the NBCN HCC group, 61 patients succumbed after 2 years. Subsequently, NBCN HCC patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…15,24,26,27 Moreover, DM was significantly more prevalent in patients with NASH-related cirrhosis compared to non-NASHrelated cirrhosis according to Hashizume et al and Yatsjui et al 27,38 The prevalence of DM in patients with NASH-related HCC was reported in six studies and ranged from 38 to 63%. 20,30,[39][40][41][42] Dyslipidemia. Dyslipidemia and its most common form, hyperlipidemia, are also frequently found in NAFLD and NASH patients.…”
Section: Prevalence Of Comorbiditiesmentioning
confidence: 99%
See 2 more Smart Citations
“…15,24,26,27 Moreover, DM was significantly more prevalent in patients with NASH-related cirrhosis compared to non-NASHrelated cirrhosis according to Hashizume et al and Yatsjui et al 27,38 The prevalence of DM in patients with NASH-related HCC was reported in six studies and ranged from 38 to 63%. 20,30,[39][40][41][42] Dyslipidemia. Dyslipidemia and its most common form, hyperlipidemia, are also frequently found in NAFLD and NASH patients.…”
Section: Prevalence Of Comorbiditiesmentioning
confidence: 99%
“…48 Fibrosis stage did not significantly change despite 6 of the 10 patients reporting an improvement in fibrosis stage. 48 In three studies reporting the mean fibrosis stage of patients with NASH-related HCC, the score ranged from 2.30 to 3.20 based on Brunt 30,40,49 and New Inuyama scoring. 30,40,49 Iida et al observed the fibrosis stage of HCC patients according to HCC etiology and reported no significant difference in mean fibrosis between NASH (2.30), alcoholic liver disease (ALD) (2.20), and non-NASH non-ALD (2.40).…”
Section: Prevalence Of Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…HCV infection alters lipid metabolism and leads to dyslipidemia, hepatic steatosis and advanced fibrosis . Persistent viral infections tend to induce liver dysfunction and may further result in cirrhosis and hepatocellular carcinoma . Hepatic steatosis is one of the primary aetiologies of induced liver diseases.…”
Section: Introductionmentioning
confidence: 99%
“…3 Persistent viral infections tend to induce liver dysfunction and may further result in cirrhosis and hepatocellular carcinoma. 4,5 Hepatic steatosis is one of the primary aetiologies of induced liver diseases. Compared to other chronic liver diseases, the occurrence of hepatic steatosis is prevalent in patients with chronic hepatitis C. 6 The core protein of HCV localizes to the surface of lipid droplets and contributes to hepatic steatosis by interfering with intracellular lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%